Analisis Kontrastif Proses Afiksasi pada Bahasa Indonesia dan Bahasa Korea untuk Pengajaran BIPA - Sintaningrum, Tiara Putri; Muhyidin, Asep; Senjaya, Arip (Universitas Muhammadiyah Surabaya, 2025)
This research focuses on the affixation process between Indonesian and Korean. This research was motivated by the mistakes and difficulties of Korean BIPA students regarding the formation and use of the affixes meN-, peN-, and di-. The data of this research were in the forms of Indonesian and Korean affixes found in I Want to Die but I Want to Eat Tteokpokki. The qualitative descriptive approach was used with intralingual matching method to analyze the data. The data were collected using literature studies, data interpretation, and note-taking techniques. The data used in Indonesian were 196 data while in Korean 35 data. The results of the study found two differences and two similarities between Indonesian and Korean affixation. The affixation process in Indonesian causes changes in word classes, affix forms, and base word forms. While, in Korean just base word forms has changed. Another similarity is found in the form of Indonesian and Korean affixes which have the same form as other morphemes.